Habitat requirements and germination performance of some relict populations of Ligularia sibirica (Asteraceae) from Romania - Alina Cîșlariu; Ciprian Mânzu; Maria Zamfirache (Plant Ecology and Evolution, 2018)
Background and aims – Ligularia sibirica is a glacial relict plant species in Europe. Its populations are rare and endangered in most of the European localities. Studies on glacial relics are insufficient; among them only a few focus on the population characteristics and their reproductive capacity. We aimed to determine the habitat requirements of L. sibirica populations; which factors affect the reproductive output of the populations and how the interaction of ecological and biological parameters influences their germination capacity.Methods – We described habitat conditions in terms of the Ellenberg indicators (for nitrogen availability, moisture, light, soil reaction, and temperature) in each analysed population. To determine which factors affect the population viability we performed a series of regression analyses. Germination experiment was carried under laboratory-controlled conditions at a 14/10 h. photoperiod and 24/16°C temperature, for 32 days, with cold stored seeds (at 4°C), and seeds stored at room temperature on a different substrate (moist filter paper and oligotrophic soil). The parameters influencing population germination rate were determined with general linear models. Key results – We found that the soil humidity, nitrogen availability, temperature, and lighting are the ecological factors influencing the morphological features of L. sibirica populations. The largest seeds are in the middle part of the inflorescence though this parameter has no influence on germination rate. The seeds germinated better on moist filter paper. Cold stored seeds did not show higher germination rate. Germination increased with the altitude of the populations and the seeds mass, whilst higher values of density had a negative influence on it. Conclusions – Our results suggest that habitat conditions and population characteristics are highly related to the germination success of L. sibirica. The prosperity of a population (expressed by the number of individuals) is not a guarantee of reproductive success, the densest populations having the lowest rates of germination.